L’instrumentalisation de la religion dans l’Empire ottoman à l’époque de l’expansion européenne (1800-1914) - Paul Dumont (European Journal of Turkish Studies)
This article focuses on the use of religion by the Ottoman central power in order to prevent the loss of territories (and populations) from the end of the 18th century until the beginning of the 20th century. Especially after the Treaty of Küçük Kaynarca, the Ottoman ruler and his entourage decided to use his caliphal status in two different directions. On the one hand, the symbolic leadership of the Ummah claimed by the Sultan was mobilized in remote Muslim territories in order to obtain external allies; on the other hand, the Sublime Porte instrumentalized the title of Caliph to make Western powers accept that albeit lost, territories comprising Muslim populations formerly under Ottoman rule would remain under the religious jurisdiction of the Sultan. Implemented from the last decades of the 18th century onwards, this policy has been relatively successful. The various bilateral or multilateral treaties to which the Ottoman government was a party resulted in the establishment of strong and durable ties between Muslims of regions that were previously part of the Ottoman Empire, such as Greece, Bulgaria, Bosnia or Crimea.